2016
DOI: 10.1111/add.13254
|View full text |Cite
|
Sign up to set email alerts
|

Validity of the alcohol purchase task: a meta‐analysis

Abstract: The Alcohol Purchase Task appears to have good construct validity, but limited incremental utility in estimating risk for alcohol problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
61
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(75 citation statements)
references
References 38 publications
(54 reference statements)
14
61
0
Order By: Relevance
“…Secondly, with respect to modeled dimensions of the demand curve, demand intensity appears to provide stronger associations than elasticity. This difference has been observed for illicit substances, as described here, and with alcohol, as described previously . Several reasons for this finding are possible.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Secondly, with respect to modeled dimensions of the demand curve, demand intensity appears to provide stronger associations than elasticity. This difference has been observed for illicit substances, as described here, and with alcohol, as described previously . Several reasons for this finding are possible.…”
Section: Discussionsupporting
confidence: 85%
“…An underlying assumption of behavioral economic demand is that there are individual differences in reinforcer value that demand measured by the purchase task procedure can reveal. As noted above, prior meta‐analytical work has highlighted this utility and sensitivity to individual differences in quantity–frequency (QF) and severity of alcohol use for the alcohol purchase task . The purpose of this analysis was to similarly synthesize the purchase task literature with illicit compounds for the first time.…”
Section: Introductionmentioning
confidence: 99%
“…We also relied on data collected as hypothetical preferences rather than actual, real‐world preferences. Prior research in substance use has revealed that hypothetical tasks show good correspondence with incentivized versions and demand in simulated procedures corresponds to real‐world measures cross‐sectionally and prospectively (Amlung, Acker, Stojek, Murphy, & MacKillop, ; Dennhardt, Yurasek, & Murphy, ; Kiselica, Webber, & Bornovalova, ; Murphy et al, ; Strickland, Alcorn III, & Stoops, ). Additional research evaluating the relationship between condom demand and prospectively collected, real‐world health behaviors will be important for demonstrating similar predictive and ecological validity.…”
Section: Discussionmentioning
confidence: 94%
“…Results support previous research such that approach inclinations were positively associated with all indices of demand except P max . The lack of association with P max was not a surprise, given that P max tends to exhibit non-significant relationships with drinking behavior (Kiselica et al, 2016). Importantly results also suggest that avoidance inclinations account for significant variance above and beyond approach inclinations on several indices of alcohol demand (O max , breakpoint, elasticity), and that avoidance moderates the effect of approach motivation for both O max and breakpoint.…”
Section: Discussionmentioning
confidence: 99%
“…While these demand indices are functionally related to one another, theoretically they reflect distinct measures of reinforcement (Bickel, Marsch, & Carroll, 2000). More importantly, in a recent meta-analysis of studies using the APT, while some effect sizes were small, all indices of demand had significant associations with alcohol consumption, alcohol-related problems, and/or AUD symptoms (Kiselica, Webber, & Bornovalova, 2016). Further, intensity and O max tend to exhibit the most robust associations with drinking behavior and alcohol-related problems (MacKillop & Murphy, 2007; Murphy et al, 2009).…”
Section: Introductionmentioning
confidence: 99%